An analysis of cohesive Devices in Sa'di's Būstān and its aesthetic impact within the framework of Halliday's systemic functional theory - Omid Azad (مطالعات زبانی و بلاغی)
Halliday’s cohesive theory is one of the most important theories in functional linguistics, extensively used for the analysis of diverse literary texts. Based on this theory, logical, semantic, grammatical as well as formal relationships create cohesion in a text; hence, textual cohesion is classified into grammatical, lexical and connective subcategories. Grammatical cohesion includes reference, substitution and ellipsis while two subcategories of reiteration and collocation shapes lexical cohesion. Sa'di's verbal art is so enriched that meaning is not sacrificed for the sake of form, nor is form sacrificed for the sake of meaning. The poet's dexterity in the Persian literature's lexical and grammatical subtleties, and appropriate and skillful use of literary devices has made his poetry distinctive. In this descriptive-analytical research, adopting Halliday's theory of cohesion, one verse anecdote from the Būstān (The Fox and the Dervish) is selected to analyze the use of cohesive devices across three linguistic layers. Although cohesion in Sa'di's ghazals has been widely acknowledged, the reasons behind the cohesive strength of the verse anecdotes in the Būstān have not been thoroughly examined from a systemic functional perspective. Hence, the main research question was how lexical, grammatical and connective devices were employed in Sa'di's poetry, and which device was emphasized the most. The results corroborated the extensive and diverse use of cohesive devices in the verse anecdotes, in which the use of lexical cohesive devices is most outstanding. Among the grammatical devices, the poet puts more emphasis upon reference and ellipsis respectively. Furthermore, the poet's dexterous use of lexical cohesive devices, particularly repetition and its various forms on one hand, and collocation on the other hand, enhanced the beauty of the poet's expression, aiding its impact and facilitating better meaning transfer, so that form serves the purpose of meaning.  Among cohesive connective, additive and causative were the most prominent linguistic elements. This conclusion is in accordance with the characteristics of Sa'di's poetry as simplicity, lexical beauty, and fluency are outstanding features of this version of Iraqi style. Therefore, from a practical perspective, Halliday's theory is considered an appropriate framework for identifying cohesive devices in the prestigious poetic and prose texts of Persian literature, such as the Būstān. Based on the way cohesive devices are employed by various poets and literary figures, one may be able to understand, from the perspective of meaning, the organization of their thoughts and the originality of their ideas, and from the perspective of form, the unique verbal and rhetorical styles of each poet.